الحركة الفكرية في مدينة شنترين Santarem الأندلسية - العلياوي، حسين جبار مجيتل; الدرويش، جاسم ياسين محمد (الجامعة الإسلامية, 2023)
فتح المسلمون مدينة شنترين في حدود سنة 95ه/713م واستمرت تحكم من قبلهم حتى سقوطها بيد نصارى البرتغال سنة 542ه/1147م، أي ما يقارب 447 سنة، وطيلة تلك المدة طبعت المدينة بالطابع العربي الإسلامي، فظهر فيها العديد من رجال الفكر في مختلف حقول المعرفة، ومما ساعد على ازدهار الحركة الفكرية فيها أنها كانت منطقة ثغرية مواجهة لأعداء المسلمين، فكان يرتادها العديد من العلماء بقصد المرابطة فيها للجهاد، كما كان لجمال المدينة ومنطقتها عاملا ساعد على تفجر قرائح الأدباء والشعراء في وصف تلك المناظر الخلابة وهم يتجولون في بين المياه والخضرة والنسائم الطيبة، فكان منهم من اشتهر برواية الحديث والقراءات القرآنية، ومنهم من اشتهر باللغة والأدب وعلى رأسهم الأديب أبي الحسن علي بن بسام الشنتريني صاحب أشهر مصنفي كتب الأدب في الأندلس. The Muslims conquered the city of Santarem in about the year 95 AH / 713 AD, and it continued to be ruled by them until it fell under the control of the Christians of Portugal in the year 542 AH/ 1145 AD, which is approximately 447 years. During that period, the city changed with the Arab-Islamic manifestations, so many men of thought appeared in it in various fields of knowledge, and what helped the intellectual movement to flourish in it was that it was a frontal area facing the enemies of Muslims, so many scholars used to frequent it with the intention of stationing there for jihad, as was the beauty of the city and its region A factor that helped erupt the minds of writers and poets in describing those picturesque scenes as they wandered among the waters, greenery, and pleasant breezes. Some of them were famous for narrating hadiths and Quranic readings, and some of them were famous for language and literature, the first of whom was the writer Abi al-Hasan Ali bin Bassam al-Shantarini, the author of the most famous author of literature books in Andalusia.
Keywords: التاريخ الإسلامي -- الحركة الفكرية -- الثقافة الإسلامية -- بلاد الأندلس